Socioeconomic Residential Segregation and Income Inequality in Bogotá: An Analysis Based on Census Data of 2005 (2021)
Residential segregation is both a cause and consequence of socioeconomic inequalities. Since the 1990s, segregation patterns in Latin American cities have changed significantly. This is related to major urban transformations caused by privatization policies related to urban development, commercialization, and real estate activity. The main purpose of this chapter is to study residential socioeconomic segregation in the city of Bogotá, Colombia in 2005, using educational attainment as an indicator of socioeconomic status while considering the drivers of segregation during the 1990s. We also introduce a brief analysis of the relationship between residential segregation and inequality based on a model that allows replicating the income distribution of the population using census variables. This chapter shows that residential segregation in Bogotá is related to per capita income inequality, however, segregation may be caused by the dynamics of land and housing markets rather than inequality. Keywords Socioeconomic residential segregation · Income inequality · Bogotá